Outcome of fetuses with short femur length detected at second‐trimester anomaly scan: a national survey. (27th June 2014) - Mathiesen, J. M.; Aksglaede, L.; Skibsted, L.; Petersen, O. B.; Tabor, A.; the Danish Fetal Medicine Study Group; Jørgensen, Finn Stener; Larsen, Torben; Mogensen, Helle; Hoseth, Eva; Sommer, Steffen; Sperling, Lene Søndergaard; et al.
ABSTRACT Objective To assess the relationship between the finding of fetal femur diaphysis length (FL) below the 5th percentile at the second‐trimester scan and pregnancy outcome, in a population in which more than 90% of women attend first‐trimester screening. Methods This was a retrospective study of all Danish singleton pregnancies with a 17–22‐week anomaly scan between 1 January 2008 and 30 June 2011. Information on FL and gestational age (GA) at anomaly scan, on birth weight and GA at delivery and on chromosomal abnormalities was obtained from the Danish Fetal Medicine Database. Results Short FL was identified in 2718 (1.8%) of 147 766 fetuses and was present in 11 (16.2%) of the 68 fetuses affected by trisomy 21 (positive likelihood ratio (LR+) 8.8 (95% CI, 5.1–15.2)). Trisomy 13/18 and unbalanced autosomal structural abnormalities were also associated with a short FL in three (12.0%, LR+ 6.5 (95% CI, 2.3–18.9)) and eight (32.0%, LR+ 17.4 (95% CI, 9.8–30.9)) of the cases, respectively. The risk of a fetus having trisomy 21, trisomy 18, trisomy 13 or an unbalanced autosomal structural abnormality was 1 : 123 (95% CI, 79–192), given a short FL. Pregnancies with a fetus with short FL were more often affected by early preterm delivery (before 34 weeks) (5.6%; odds ratio (OR) = 4.2 (95% CI, 3.5–4.9)) and small‐for‐gestational‐age (SGA) infants (13.9%; OR = 4.3 (95% CI, 3.8–4.8)). Conclusion Short FL at the second‐trimester anomaly scan is associated with a significantly higher relative risk of chromosomal abnormalities, and a substantially higher absolute risk for SGA and early preterm delivery. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd